Antibody response after COVID-19 vaccine BNT162b2 on health care workers in Japan. Issue 12 (December 2021) - Yoshimura, Yukihiro; Sasaki, Hiroaki; Miyata, Nobuyuki; Miyazaki, Kazuhito; Tachikawa, Natsuo
Abstract: Background: Vaccination is one of the most important tools to control the COVID-19 pandemic. However, there is little information on the antibody response in humans after the COVID-19 vaccination. Methods: This single-center, prospective study was conducted in Yokohama, Japan. We included health care workers who had received two doses of COVID-19 vaccination (BNT162b2) 21 days apart. We measured serum immunoglobulin G (IgG) to nucleoprotein and spike protein of SARS-CoV-2 with commercially available kits before and 7, 14, and 35 days after the first dose of vaccination. Results: A total of 104 workers participated in this study. Of these, 7 participants were seropositive with antibodies to spike protein at baseline and 4 of the 7 seropositive participants had COVID-19 history. The mean level of IgG to spike protein (QT) was 45.2, 1219, 2845, and 23489 AU/mL at baseline, on days 7, 14, and 35, respectively, although the values for nucleoprotein (NG) were 0.2, 0.21, 0.22, and 0.19 S/C, respectively. On day 7, QT in seropositive participants at baseline was elevated, whereas it was not elevated in seronegative participants at baseline until day 14. Conclusions: QT was elevated over the cutoff in all the participants at day 35, but NG did not change between baseline and day 35.